Targeting Acidic Diseased Tissues by pH-Triggered Membrane-Associated Peptide Folding - Reshetnyak, Yana K.; Moshnikova, Anna; Andreev, Oleg A.; Engelman, Donald M. (Frontiers in Bioengineering and Biotechnology, 2020)
The advantages of targeted therapy have motivated many efforts to find distinguishing features between the molecular cell surface landscapes of diseased and normal cells. Typically, the features have been proteins, lipids or carbohydrates, but other approaches are emerging. In this discussion, we examine the use of cell surface acidity as a feature that can be exploited by using pH-sensitive peptide folding to target agents to diseased cell surfaces or cytoplasms.